Postharvest technology and food process engineering [ - Chakraverty, Amalendu; Singh, R. Paul (CRC Press, 2014)
Cereals, legumes, oilseeds, fruits, and vegetables are the most important food crops in the world, with cereal grains contributing the bulk of food calories and proteins worldwide. Generally, the supply of grains and other food can be enhanced by increasing production and by reducing postharvest losses. While food production has increased significantly over the last few decades, minimizing huge postharvest losses as well as utilizing their by products/wastes is the optimal way for a country to become self-sufficient in food.